Impact of artificial intelligence on the achievement of sustainable development goals across China - Li, Chenggang; Pan, Xiaopiao; Yue, Mu; Ge, Jianjun; Wang, Wenqi; Zhao, Guanghui (Frontiers in Environmental Science, 2026)
IntroductionThe rapid development of artificial intelligence (AI) technology has become a key driver in achieving the Sustainable Development Goals (SDGs). However, systematic quantitative researches about the impact and pathway of artificial intelligence on the achievement of SDGs are still relatively limited.MethodsBased on the penal data of 30 provinces (autonomous regions and municipalities) in China from 2010 to 2023, this study uses the entropy method to calculate evaluation index of SDG indicators, and systematically examines the impact and pathway of artificial intelligence (measured by the installation density of industrial robots) on achieving SDGs through the two-way fixed effect model, the mediation effect model, and spatial error model.ResultsThe study finds that artificial intelligence has markedly promoted the achievement of China’s overall SDGs and it has a continuously increasing cumulative effect. This driving effect varies across different SDGs, and is most significant in economic growth (SDG8 and SDG9) and climate action (SDG13). The effect of artificial intelligence on achieving SDGs is more pronounced in eastern regions, regions with better SDGs performance, and regions with a late start in artificial intelligence development. Technological innovation and human capital optimization are important ways through which artificial intelligence affects the achievement of SDGs and can further enhance its positive role. Spatial analysis reveals significant positive spatial agglomeration in both AI and SDGs, along with potential spatial dependence across regions driven by unobserved factors.DiscussionThis study provides useful decision-making references for formulating differentiated and inclusive artificial intelligence policies, and promoting the achievement of SDGs.